Molybdenum alloy surface anti-cracking coating and preparation method thereof
A molybdenum alloy anti-cracking coating is prepared by surface treatment and slurry sintering, addressing cracking issues through Zr and B's oxygen reaction, ensuring high-temperature stability and industrial applicability.
Patent Information
- Application Number
- CN202411355214.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-27
AI Technical Summary
Molybdenum alloys suffer from low-temperature brittleness, low room temperature recrystallization temperature, and poor high-temperature oxidation resistance, leading to cracking issues due to thermal expansion coefficient differences between the alloy and its coatings.
A method involving surface preparation, mixing specific powders (Si, ZrB2, B, SiC, MnO2, and a sintering aid) followed by slurry coating and vacuum sintering to create an anti-cracking coating on molybdenum alloys, with Zr and B reacting with oxygen to enhance crack prevention.
The coating effectively prevents further cracking under high temperatures, is suitable for substrates of any size, and is cost-effective with a simple process suitable for industrialization.
Smart Images

Figure CN119243157A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal coating preparation, and specifically relates to a molybdenum alloy surface anti-cracking coating and a preparation method thereof. Background Art
[0002] Molybdenum alloys have excellent properties such as high melting point, high creep resistance, high thermal conductivity and low thermal expansion coefficient. However, molybdenum alloys have defects such as low-temperature brittleness, low room temperature recrystallization temperature and poor high-temperature oxidation resistance. These defects make molybdenum alloys unable to serve for a long time. The commonly used methods are alloying and coating preparation. However, alloying is difficult to achieve due to its restrictions on the substrate, so coating is more commonly used. However, the existing coating and substrate are very prone to cracking due to the large difference in thermal expansion coefficient. Therefore, it is urgent to develop a molybdenum alloy surface anti-cracking coating that can effectively prevent cracking. Summary of the invention
[0003] In order to solve the problems existing in the prior art, the main purpose of the present invention is to provide a molybdenum alloy surface anti-cracking coating and a preparation method thereof.
[0004] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:
[0005] A method for preparing a molybdenum alloy surface anti-cracking coating comprises the following steps:
[0006] S1, grinding the surface of the molybdenum alloy substrate with sandpaper, cleaning the impurities on the surface with anhydrous ethanol, and then drying to obtain the treated molybdenum alloy substrate;
[0007] S2, mixing Si, ZrB2, B, SiC, MnO2, and sintering aid powders in a certain ratio to obtain a mixed powder, and performing wet ball milling to mix the mixed powder to prepare a uniform slurry;
[0008] S3, coating a slurry coating with uniform thickness on the treated molybdenum alloy substrate by a spray coating process, and drying the substrate after natural drying to obtain a dried body;
[0009] S4. Place the dried green body into a pre-burned crucible and sinter it in a vacuum sintering furnace to obtain an anti-cracking coating on the surface of the molybdenum alloy.
[0010] As a preferred embodiment of the method for preparing a molybdenum alloy surface anti-cracking coating described in the present invention, in which: in the step S2, the mixed powder comprises, by mass percentage, Si: 20-60%, ZrB2: 5-30%, B: 5-30%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid.
[0011] As a preferred embodiment of the method for preparing a molybdenum alloy surface anti-cracking coating according to the present invention, in step S2, the sintering aid is PVB.
[0012] As a preferred embodiment of the method for preparing a molybdenum alloy surface anti-cracking coating according to the present invention, wherein: in the step S2, anhydrous ethanol is added for wet ball milling, the ball milling speed is 300 rpm, and the ball milling time is 6 hours.
[0013] As a preferred embodiment of the method for preparing a molybdenum alloy surface anti-cracking coating according to the present invention, in said step S3, the air pressure of the spray gun during spraying is 0.8 MPa, the spraying distance is 100 mm, and the drying time is 2.0 h.
[0014] As a preferred embodiment of the method for preparing a molybdenum alloy surface anti-cracking coating according to the present invention, in step S3, the thickness of the slurry coating is 120-200 μm.
[0015] As a preferred embodiment of the method for preparing a molybdenum alloy surface anti-cracking coating according to the present invention, in step S4, the sintering temperature is 800° C., the sintering time is 1 hour, and the sintering is performed in an argon atmosphere.
[0016] To solve the above technical problem, according to another aspect of the present invention, the present invention provides the following technical solution:
[0017] A molybdenum alloy surface anti-cracking coating is prepared by adopting the above-mentioned method for preparing the molybdenum alloy surface anti-cracking coating.
[0018] As a preferred embodiment of the anti-cracking coating on the surface of a molybdenum alloy described in the present invention, the thickness of the anti-cracking coating is 100-180 μm, and the coating mass changes by ≤4.0 g after high-temperature oxidation at 1000-1200° C. for 1 h.
[0019] The beneficial effects of the present invention are as follows:
[0020] The present invention proposes a molybdenum alloy surface anti-cracking coating and a preparation method thereof. On the basis of the silicide coating, two alloy elements Zr and B are added. Under high temperature conditions, the B element and the Zr element react with oxygen, and the product thereof can effectively prevent further cracking of the coating. The present invention adopts the method of slurry sintering to prepare the coating, which can protect substrates of any size. At the same time, the equipment cost is low, the process is simple, and it is easy to realize industrialization. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0022] Figure 1 This is a SEM image of the coating surface of Example 1 of the present invention;
[0023] Figure 2 is a SEM image of a cross section of the coating of Example 1 of the present invention;
[0024] Figure 3 This is a SEM image of the coating surface of Comparative Example 1 of the present invention;
[0025] Figure 4 This is a SEM image of the coating cross section of Comparative Example 1 of the present invention.
[0026] Figure 5 This is a SEM image of the coating surface of Comparative Example 2 of the present invention;
[0027] Figure 6 This is a SEM image of the coating cross section of Comparative Example 2 of the present invention.
[0028] Figure 7 This is a SEM image of the coating surface of Comparative Example 3 of the present invention;
[0029] Figure 8 This is a SEM image of the coating cross section of Comparative Example 3 of the present invention.
[0030] Fig. 9 The graphs are of mass changes of samples of various embodiments of the present invention at different oxidation temperatures.
[0031] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0032] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The present invention provides a molybdenum alloy surface anti-cracking coating and a preparation method thereof. On the basis of a silicide coating, two alloy elements, Zr and B, are added. Under high temperature conditions, the B element and the Zr element react with oxygen, and the product thereof can more effectively prevent further cracking of the coating.
[0034] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0035] Example 1
[0036] A method for preparing a molybdenum alloy surface anti-cracking coating comprises the following steps:
[0037] S1. After grinding the surface of the molybdenum alloy substrate with 400-2000# sandpaper, the impurities on the surface are cleaned with anhydrous ethanol, and then dried to obtain the treated molybdenum alloy substrate;
[0038] S2. Mix Si, ZrB2, B, SiC, MnO2 and sintering aid powders in a certain proportion to obtain a mixed powder, and perform wet ball milling to mix and make a uniform slurry; the mixed powder includes, by mass percentage, Si: 53%, ZrB2: 5%, B: 5%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid; the sintering aid is PVB, anhydrous ethanol is added, and the mixture is ball milled and mixed in a QM-1SP planetary high-energy ball mill, the ball milling speed is 300rpm, and the ball milling time is 6h;
[0039] S3, using a spray coating process to coat a slurry coating of uniform thickness on the treated molybdenum alloy substrate, and placing it in a vacuum drying oven for drying after natural drying to obtain a dried body; during spraying, the air pressure of the spray gun is 0.8MPa, the spraying distance is 100mm, the drying time is 2.0h, and the thickness of the slurry coating is 135μm;
[0040] S4. The dried green body was placed in a pre-burned crucible and sintered in a vacuum sintering furnace at a temperature of 800°C for 1 h in an argon atmosphere. An anti-cracking coating was obtained on the surface of the molybdenum alloy with a thickness of 134.02 μm. The SEM image of the surface is shown in FIG. Figure 1 As shown in Figure 2, it can be seen that the coating surface has a high density; the SEM image of the cross section is shown in Figure 2 Figure 2 As shown, no obvious micro cracks were observed.
[0041] Example 2
[0042] A method for preparing a molybdenum alloy surface anti-cracking coating comprises the following steps:
[0043] S1. After grinding the surface of the molybdenum alloy substrate with 400-2000# sandpaper, the impurities on the surface are cleaned with anhydrous ethanol, and then dried to obtain the treated molybdenum alloy substrate;
[0044] S2. Mix Si, ZrB2, B, SiC, MnO2 and sintering aid powders in a certain proportion to obtain a mixed powder, and perform wet ball milling to mix and make a uniform slurry; the mixed powder includes, by mass percentage, Si: 48%, ZrB2: 10%, B: 5%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid; the sintering aid is PVB, anhydrous ethanol is added, and the mixture is ball milled and mixed in a QM-1SP planetary high-energy ball mill, the ball milling speed is 300rpm, and the ball milling time is 6h;
[0045] S3, using a spray coating process to coat a slurry coating of uniform thickness on the treated molybdenum alloy substrate, and placing it in a vacuum drying oven for drying after natural drying to obtain a dried body; during spraying, the air pressure of the spray gun is 0.8MPa, the spraying distance is 100mm, the drying time is 2.0h, and the thickness of the slurry coating is 126.78μm;
[0046] S4. Place the dried green body into a pre-fired crucible and sinter it in a vacuum sintering furnace at a temperature of 800° C. for 1 h in an argon atmosphere to obtain an anti-cracking coating on the surface of the molybdenum alloy with a thickness of 104.41 μm.
[0047] Example 3
[0048] A method for preparing a molybdenum alloy surface anti-cracking coating comprises the following steps:
[0049] S1. After grinding the surface of the molybdenum alloy substrate with 400-2000# sandpaper, the impurities on the surface are cleaned with anhydrous ethanol, and then dried to obtain the treated molybdenum alloy substrate;
[0050] S2. Mix Si, ZrB2, B, SiC, MnO2 and sintering aid powders in a certain proportion to obtain a mixed powder, and perform wet ball milling to mix and make a uniform slurry; the mixed powder includes, by mass percentage, Si: 48%, ZrB2: 5%, B: 10%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid; the sintering aid is PVB, anhydrous ethanol is added, and the mixture is ball milled and mixed in a QM-1SP planetary high-energy ball mill, the ball milling speed is 300rpm, and the ball milling time is 6h;
[0051] S3, using a spray coating process to coat a slurry coating of uniform thickness on the treated molybdenum alloy substrate, and placing it in a vacuum drying oven for drying after natural drying to obtain a dried body; during spraying, the air pressure of the spray gun is 0.8MPa, the spraying distance is 100mm, the drying time is 2.0h, and the thickness of the slurry coating is 180.74μm;
[0052] S4. Place the dried green body into a pre-fired crucible and sinter it in a vacuum sintering furnace at a temperature of 800° C. for 1 h in an argon atmosphere to obtain an anti-cracking coating on the surface of the molybdenum alloy with a thickness of 167.41 μm.
[0053] Example 4
[0054] A method for preparing a molybdenum alloy surface anti-cracking coating comprises the following steps:
[0055] S1. After grinding the surface of the molybdenum alloy substrate with 400-2000# sandpaper, the impurities on the surface are cleaned with anhydrous ethanol, and then dried to obtain the treated molybdenum alloy substrate;
[0056] S2. Mix Si, ZrB2, B, SiC, MnO2 and sintering aid powders in a certain proportion to obtain a mixed powder, and perform wet ball milling to mix and make a uniform slurry; the mixed powder includes, by mass percentage, Si: 43%, ZrB2: 10%, B: 10%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid; the sintering aid is PVB, anhydrous ethanol is added, and the mixture is ball milled and mixed in a QM-1SP planetary high-energy ball mill, the ball milling speed is 300rpm, and the ball milling time is 6h;
[0057] S3, using a spray coating process to coat a slurry coating of uniform thickness on the treated molybdenum alloy substrate, and placing it in a vacuum drying oven for drying after natural drying to obtain a dried body; during spraying, the air pressure of the spray gun is 0.8MPa, the spraying distance is 100mm, the drying time is 2.0h, and the thickness of the slurry coating is 188.37μm;
[0058] S4. Place the dried green body into a pre-fired crucible and sinter it in a vacuum sintering furnace at a temperature of 800°C for 1 hour in an argon atmosphere to obtain an anti-cracking coating on the surface of the molybdenum alloy with a thickness of 171.71 μm. No severe oxidation occurs at a temperature of ≤1200°C.
[0059] Example 5
[0060] A method for preparing a molybdenum alloy surface anti-cracking coating comprises the following steps:
[0061] S1. After grinding the surface of the molybdenum alloy substrate with 400-2000# sandpaper, the impurities on the surface are cleaned with anhydrous ethanol, and then dried to obtain the treated molybdenum alloy substrate;
[0062] S2. Mix Si, ZrB2, B, SiC, MnO2 and sintering aid powders in a certain proportion to obtain a mixed powder, and perform wet ball milling to mix and make a uniform slurry; the mixed powder includes, by mass percentage, Si: 33%, ZrB2: 10%, B: 20%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid; the sintering aid is PVB, anhydrous ethanol is added, and the mixture is ball milled and mixed in a QM-1SP planetary high-energy ball mill, the ball milling speed is 300rpm, and the ball milling time is 6h;
[0063] S3, coating a slurry coating with uniform thickness on the treated molybdenum alloy substrate by a spray coating process, and placing it in a vacuum drying oven for drying after natural drying to obtain a dried body; during spraying, the air pressure of the spray gun is 0.8MPa, the spraying distance is 100mm, the drying time is 2.0h, and the thickness of the slurry coating is 168.86μm;
[0064] S4. Place the dried green body into a pre-fired crucible and sinter it in a vacuum sintering furnace at a temperature of 800°C for 1 hour in an argon atmosphere to obtain an anti-cracking coating on the surface of the molybdenum alloy with a thickness of 166.05 μm. No severe oxidation occurs at a temperature of ≤1200°C.
[0065] Comparative Example 1
[0066] The difference from Example 1 is that the mixed powder in step S2 includes, by mass percentage, Si: 45%, B: 18%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid.
[0067] The SEM image of the coating surface of this comparative example is as follows Figure 3 As shown in Figure 2, obvious surface cracks can be seen on the coating surface; the SEM image of the cross section is shown in Figure 2 Figure 4 As shown, the coating has coating cracking.
[0068] Comparative Example 2
[0069] The difference from Example 1 is that the mixed powder in step S2 includes, by mass percentage, Si: 62%, ZrB2: 3%, SiC: 5%, MnO2: 25%, and the remainder is a sintering aid.
[0070] The SEM image of the coating surface of this comparative example is as follows Figure 5 As shown in Figure 2, obvious surface cracks can be seen on the coating surface; the SEM image of the cross section is shown in Figure 2 Figure 6 As shown, the coating has coating cracking.
[0071] Comparative Example 3
[0072] The difference from Example 1 is that the mixed powder in step S2 includes, by mass percentage, Si: 63%, SiC: 5%, MnO2: 30%, and the remainder is a sintering aid.
[0073] The SEM image of the coating surface of this comparative example is as follows Figure 7 As shown in Figure 2, obvious surface cracks can be seen on the coating surface; the SEM image of the cross section is shown in Figure 2 Figure 8 As shown, the coating has coating cracking.
[0074] The molybdenum alloys with anti-cracking coatings on the surfaces prepared in Examples 1-5 were oxidized at 1000°C, 1100°C, and 1200°C for 1 h, respectively. The coating quality changes before and after oxidation are as follows: Fig. 9 As shown, it can be seen that at temperatures below 1200° C., the anti-cracking coating on the surface of the molybdenum alloy of Examples 1-5 does not undergo severe oxidation.
[0075] It can be seen from the above embodiments and comparative examples that the present invention adds two alloy elements, Zr and B, to the silicide coating. Under high temperature conditions, the B element and the Zr element react with oxygen, and the product thereof can effectively prevent further cracking of the coating. In addition, the present invention adopts the method of slurry sintering to prepare the coating, which can protect substrates of any size. At the same time, the equipment cost is low, the process is simple, and it is easy to realize industrialization.
[0076] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a molybdenum alloy surface anti-cracking coating, characterized in that: The steps include: S1, grinding the surface of the molybdenum alloy substrate with sandpaper, cleaning the impurities on the surface with anhydrous ethanol, and then drying to obtain the treated molybdenum alloy substrate; S2, mixing Si, ZrB2, B, SiC, MnO2, and sintering aid powders in a certain ratio to obtain a mixed powder, and performing wet ball milling to mix the mixed powder to prepare a uniform slurry; S3, coating a slurry coating with uniform thickness on the treated molybdenum alloy substrate by a spray coating process, and drying the substrate after natural drying to obtain a dried body; S4. Place the dried green body into a pre-fired crucible and sinter it in a vacuum sintering furnace to obtain an anti-cracking coating on the surface of the molybdenum alloy.
2. The method for preparing the anti-cracking coating on the surface of the molybdenum alloy according to claim 1, characterized in that: In the step S2, the mixed powder includes, by mass percentage, 20-60% Si, 5-30% ZrB2, 5-30% B, 5% SiC, 30% MnO2, and the remainder is a sintering aid.
3. The method for preparing the anti-cracking coating on the surface of the molybdenum alloy according to claim 2, characterized in that: In the step S2, the sintering aid is PVB.
4. The method for preparing the anti-cracking coating on the surface of the molybdenum alloy according to claim 1, characterized in that: In the step S2, anhydrous ethanol is added for wet ball milling, the ball milling speed is 300 rpm, and the ball milling time is 6 hours.
5. The method for preparing the anti-cracking coating on the surface of the molybdenum alloy according to claim 1, characterized in that: In step S3, the air pressure of the spray gun during spraying is 0.8 MPa, the spraying distance is 100 mm, and the drying time is 2.0 h.
6. The method for preparing the anti-cracking coating on the surface of the molybdenum alloy according to claim 1, characterized in that: In the step S3, the thickness of the slurry coating is 120-200 μm.
7. The method for preparing the anti-cracking coating on the surface of the molybdenum alloy according to claim 1, characterized in that: In the step S4, the sintering temperature is 800° C., the sintering time is 1 hour, and the sintering is performed in an argon atmosphere.
8. A molybdenum alloy surface anti-cracking coating, characterized in that: The anti-cracking coating on the surface of the molybdenum alloy is prepared by the preparation method of any one of claims 1 to 7.
9. The molybdenum alloy surface anti-cracking coating according to claim 8, characterized in that: The anti-cracking coating has a thickness of 100 to 180 μm and is subjected to high-temperature oxidation at 1000 to 1200° C. for 1 hour, and a coating mass change before and after oxidation is ≤4.0 g.
Citation Information
Patent Citations
Molybdenum-alloy MoSi2-ZrO2-Y2O3 coating, preparation method therefor and application of molybdenum-alloy MoSi2-ZrO2-Y2O3 coating
CN106116586A
Molybdenum-based composite coating and preparation method thereof
CN106853436A
Molybdenum disilicide composite coating and preparation method thereof
CN108330429A
Refractory metal high-temperature antioxidant Si-Mo-YSZ coating and preparation method thereof
CN108585897A
Coatings for molybdenum-based substrates
US20070231595A1
